Estudio del comportamiento de los monocitos en caninos tratados con auto hemoterapia - Guevara Bravo, Alexi Muriel (2023)
In this investigation we will apply the autohemotherapy technique in dogs, this field study investigates the effects caused by intramuscular autohemotherapy venous blood reinjection, on the monocytes of each dog to which this type of therapy is applied. The AHT is a technique that, after the results obtained in the different investigations, allows expanding the therapeutic possibilities of the use of blood, and is solidly based on the notion of antibodies proposed by the Nobel Prize winner Niels K. Jërne, in the Theory of Network established in 1974. This theory supports that the Immune System forms antibodies, raising the number of monocytes (and other elements of the blood that collaborate in the defense of the organism), before the reinjection of blood intramuscularly, generating an expectation of immune autoaggression, this allows explaining how a disease can be treated with antibodies from the stimulation caused by the patient's blood. In veterinary medicine, the implementation of autohemotherapy is subject to medical criteria and the management of each patient according to their pathology and species that they may present, this practice must be based on ethical principles related to animal experimentation, ATH in medicine constitutes a technique that has been used many years ago and has allowed us to contribute to the improvement and well-being of patients thanks to its therapeutic adjuvant effects, at the same time that it is an opportunity for those animals that over time have generated resistance to certain antibiotics, being a low-cost and easily accessible non-pharmacological biological therapeutic alternative. The dogs that were treated in this study were separated into two groups with different doses (5 ml - 3 ml) in order to evaluate the behavior of monocytes against each dose, although there was no statistical significance between doses due to irregularity. Of the data. But from the medical point of view, reviewing the individual results of the dogs studied, it can be observed that there was improvement in the immune system of half of the animals that were applied autohemotherapy (AHT).